An exploration into the application of specialty-orientated CBL pedagogy in undergraduate teaching in pediatric surgery - Ma, Wenyue; Gao, Hongjie; Liu, Xiaoya; Chang, Mengmeng; Jia, Changlin; Sun, Fengyin (Frontiers in Pediatrics, 2022)
Objective: This study aims to identify whether the specialty-oriented case-based learning (CBL) pedagogy contributes to the teaching of basic theory and practical operation in undergraduate clinical teaching in pediatric surgery, and to assess the satisfaction of undergraduates. Methods: A total of 72 undergraduates in Grade 2016 who interned at Qilu Hospital of Shandong University were enrolled in this study. All these undergraduates voluntarily participated in this experimental study. They were randomly divided into the experimental group (the CBL group, n=36) and the control group (the traditional lecture-based learning (LBL) group, n=36) with the assistance of random number tables. In the control group, a traditional pedagogy was adopted and the knowledge in the textbook was explained according to the syllabus. In the experimental group, a specialty-oriented CBL pedagogy was adopted under the guidance of clinical instructors. After the teaching, a comparison was drawn between both groups in respect of the theoretical exam and practical exam scores. In addition, the teaching results were evaluated by a questionnaire survey. Results: The average theoretical exam scores and comprehensive scores of undergraduates in the CBL group were higher than those in the LBL group (P<0.05). There was no significant difference in the practical exam scores between the CBL group and the LBL group (P>0.05). However, those undergraduates in the CBL group attained higher scores in doctor-patient communication and perioperative diagnosis and treatment (P<0.05). According to the questionnaire survey, the undergraduates in the CBL group had higher satisfaction than those in the LBL group. Besides, this specialty-oriented CBL pedagogy had higher performance in improving their ability to solve problems independently and cultivating and expanding their knowledge compared with the traditional pedagogy. Meanwhile, this specialty-oriented CBL pedagogy can cultivate the critical thinking of undergraduates, which could increase their learning efficiency and improve their interest in learning. Conclusion: This specialty-oriented CBL pedagogy could improve the mastery of professional knowledge, course satisfaction, doctor-patient communication ability in clinical practice, and perioperative diagnosis and treatment ability of these undergraduates. Therefore, it is worthwhile to recommend and popularize this pedagogy in undergraduate clinical teaching in pediatric surgery.